THE IMPACT OF FINANCIAL CAPITAL AND SOCIAL CAPITAL ON TECHNICAL EFFICIENCY OF CAPTURE FISHERIES IN EAST JAVA OF INDONESIA - Efani A.; Sari M.; Farizi W.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
This study aims to estimate the impact of financial and social capital on capture fisheries activity. This study was conducted in Malang Regency, East Java of Indonesia. The data was collected from 100 fishermen using face to face interview and structured questionnaire. Furthermore, the data was analysis by data Envelopment analysis (DEA) to estimate the technical efficiency of fishermen, and tobit regression to estimate the effect of financial and social capital on the technical efficiency level. The DEA indicated that fishermen's technical efficiency remain low, the average value is about 0.652. In addition, the Tobit regression show fishermen's ethnic, and infestation was positively and significantly affected the fishermen technical efficiency level.